Filling the Blank Space of Global Art Peripheries: Measurements of Art Mobility and their Ambivalence in Nairobi, Kenya - (:unkn) unknown (My University, 2013)
In recent years, art made in Africa, particularly in the metropolitan context, has witnessed a substantial increase in attention coming from transnational institutions. While many researchers have pointed out the deceitful nature of contemporary art's globalization, this turn of events still challenges the way we conceive the space of contemporary art. In this paper I use cartography as a critical tool to approach the international mobility facilitated by two art organizations based in Nairobi, Kenya.
Keywords: African Research